The impact of political pressures on sport and athletes in Montenegro - Begovic, M.; Bardocz-Bencsik, M.; Oglesby, C. A.; Dóczi, T. (Sport in Society: Cultures, Commerce, Media, Politics, 2021)
This paper addresses the impact of political pressures on sport and athletes in Montenegro, as these pressures impact the legal and the policy framework as well as the institutional settings in sport. The theoretical location of this paper is found within new institutionalism merging historical institutionalism, reviewing the structures which remain intact for many years, and rational choice institutionalism, disclosing the action of particular decision-making authorities dominantly through the policy or normative framework. This paper shows that it is not possible to clearly draw the line between political, mostly partisan, influence and the expected autonomy of the sport movement. In this constellation, institutions adopted mechanism and norms to homogenize the behavior of actors with the ability to sustain over time. Change of the institutional setting reflects adaptability to remain at the source of power. Further, the results indicate that current institutional setting, as a product of an inherited one-party political system, produced a normative framework and organizational structure which limits athletes` development and significantly reduces the democratic capacity of the sport movement.